Peningkatan Kemampuan Guru Dalam Menggunakan Model Pembelajaran pada Masa Pandemi Covid 19 Melalui Supervisi Akademik di SDN 146/X Tanjung Solok Tahun Ajaran 2021/2022 - Neni Rosnita (Departement of Mathematics Education, 2022)
This study aims to obtain information and discuss about improving the ability of teachers to use learning models during the covid 19 pandemic through academic supervision at SDN 146/X Tanjung Solok. This research is school action research which consists of two cycles. This research was carried out at SDN 146/X Tanjng Solok in the odd semester of the 2020/2021 academic year with 7 teachers as research subjects. Data collection techniques using observation, field notes and documentation. Data were analyzed using percentages and data reduction. The results showed that through the application of academic supervision, teachers could improve the ability of teachers to apply learning models at SDN 146/X Tanjung Solok during the covid 19 pandemic.